2005
DOI: 10.1111/j.1365-294x.2005.02727.x
|View full text |Cite
|
Sign up to set email alerts
|

Native breeds demonstrate high contributions to the molecular variation in northern European sheep

Abstract: Population contribution to genetic diversity can be estimated using neutral variation. However, population expansion or hybridization of diverged ancestries may weaken correlation between neutral and non-neutral variation. Microsatellite variation was studied at 25 loci in 20 native and 12 modern or imported northern European sheep breeds. Breed contributions to total gene diversity, allelic richness and mean allele-sharing distance between individuals were measured. Indications of changes in population size a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 46 publications
6
80
6
Order By: Relevance
“…Tapio et al (2005) found similar allelic richness studying European sheep (2.62-6.26). In Romanian Tsigai 7.52 alleles per breed were detected (Peter et al, 2007).…”
Section: Populationsupporting
confidence: 60%
“…Tapio et al (2005) found similar allelic richness studying European sheep (2.62-6.26). In Romanian Tsigai 7.52 alleles per breed were detected (Peter et al, 2007).…”
Section: Populationsupporting
confidence: 60%
“…A set of 15 microsatellites available for all breeds (refer to [25]) was used for the calculation. The analysis was done using DISPAN [12].…”
Section: Discussionmentioning
confidence: 99%
“…Two sheep breeds from Ukraine (Carpathian Mountain and Sokolsk), two from Russia (Russian Tsigai and Romanov) and one from Finland (Finnsheep), described by Tapio et al [25,26], were included in the analysis of breed relationships.…”
Section: Animals Dna Extraction and Microsatellite Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Although information was obtained on 34 shorttailed breeds originating in Northern Europe, it should be kept in mind that several of them are now rare and endangered and continued efforts are needed to conserve their great genetic diversity (Tapio, 2006). Breeds with North European short-tail ancestry such as the Estonian Ruhnu, the Estonian Saaremaa, the Lithuanian Native Coarsewooled and the Norwegian Grey Troender sheep (Tapio et al, 2005a and2005b;Zapasnikiene and Nainiene, 2008), and possibly the -E-mail: ord@bondi.is Herdwick sheep in the United Kingdom (Ryder, 1983), are not classified as short-tails, presumably due to their longer tails as a results of crossing with long-tailed breeds. Thus, they could not be included in the survey.…”
Section: Introductionmentioning
confidence: 99%